Validity and reliability of automotive consumer-based brand equity and consumer response measurement scales - Adetunji, Raji Ridwan; Mohd Rashid, Sabrina; Ishak, Mohd Sobhi (Akademia Baru, 2017)
Developing and managing brand equity are top priorities for many organizations because brands are one of the most valuable organizational assets. ConsumerBased Brand Equity (CBBE) also explains how brand knowledge and brand associations influence consumers’ behaviors and consumer responses. The extant literature is filled with different types of models and scales for measuring CBBE. However, the literature on CBBE has not been able to produce a measurement scale that is employable universally across industries and different contexts. Subsequently, in view of the economic, technological and sociological importance of the automotive industry, this study attempts to assess the validity and reliability of measurement scales for Automotive CBBE and Consumer Response.The Content Validity Index (CVI) of both the items-level and the scale-level CVIs from the ratings of seven (7) experts revealed that the items in the scale proposed have good content validity. Furthermore, with the use of the Exploratory Factor Analysis (EFA) with Varimax rotation, the study presents a total of 48 items for measuring Automotive CBBE and 7 items for Consumer Response. Finally, the findings also demonstrate that the validated scales have acceptable values of reliability test.